Behavioral Finance as An Alternative Concept in Investor-Related Risk for Residential Projects : A Literature Review - Aditya Sutantio; I Putu Artama Wiguna (Institut Teknologi Sepuluh Nopember, 2017)
Stakeholder is a very important factor for project success. As part of external and the most influential project stakeholder, investor as a market agent, with embedded needs, preferences and behavior might become critical project risks and should be identified and managed properly as a key project objective. This paper investigates previous studies to examine and to understand the mechanisms of investor’s economic behavior as the risk factor and its impact for the development of residential project. Traditional financial theory in the past decades generally emphasizes the rational model in investor’s decision-making without involving emotional aspect of behavior. Recently there are many scientists proposed the theory of behavioral finance which combines insight from psychology and sociology into finance and investment with the market fundamental perspective. Based on the review, we conclude that behavioral finance can be considered as an alternative concept in assessing residential project risk especially in economic volatility.